Interpreting built cityscape: Deconstructing the metaphorical messages of futuristic buildings. (November 2016) - Heinonen, Sirkka; Minkkinen, Matti
Highlights: Examples of futuristic buildings representing various metaphors are given. Causal layered analysis is applied to deconstruct metaphorical messages of buildings. Buildings as messengers of future-related meanings are discussed. Conventional metaphors present used futures, novel metaphors present alternative futures. Abstract: This article examines the metaphorical messages and interpretations of futuristic buildings and construction projects, with examples from several parts of the world, especially from Europe and Asia. Based on the research material gathered in the MEDEIA project, some examples of buildings representing various metaphors will be provided together with reflections on their implications and interpretations from an individual and societal point of view. 1 The method of causal layered analysis (CLA) is applied in the analysis to deconstruct the messages of the buildings and to illustrate the connections between their manifest appearance and the underlying metaphors. The article addresses two central questions. Firstly, how does a building, in addition to its main functions, act as a messenger and mediator of future-related meanings by embodying different types of metaphors? Secondly, which kinds of buildings present conventional metaphors and used futures, and which kinds of buildings suggest novel metaphors and alternative futures?